Diyonumo Island Tourism Potential Using Geographic Information System Application in Gorontalo Utara Regency - Ratna Amir; Ahmad Syamsu Rijal; Risman Jaya (Universitas Negeri Semarang, 2023)
One of the new tourist objects in North Gorontalo Regency is Diyonumo Island and until now it has not been optimally developed both in terms of its feasibility as a tourist area. So it really needs intervention from both the government and the private sector to encourage tourism development in North Gorontalo Regency which is based on nature. But there is no information system that provides an overview of this tourism potential. So the researchers identified the tourism potential of Diyonumo Island using a geographic information system in North Gorontalo Regency. The method used in this study was SWOT integrated with a spatial approach to analyze each parameter, namely attractions, infrastructure and accessibility. Based on spatial mapping, Diyonumo Island tourism can be recommended as a strategic tourism area for Gorontalo Province. The results of the analysis show that Diyonumo Island has a percentage of 40% of tourist attractions that have the potential to be developed and become a supporting strategy to increase the number of tourist visits.